Micro(nano)plastics Prevalence, Food Web Interactions, and Toxicity Assessment in Aquatic Organisms: A Review - Benson, Nsikak U.; Agboola, Omowumi D.; Fred-Ahmadu, Omowunmi H.; De-la-Torre, Gabriel Enrique; Oluwalana, Ayodeji; Williams, Akan B. (Frontiers in Marine Science, 2022)
Plastic pollution is a fast-rising environmental catastrophe. Microplastics and nanoplastics (MNPs) are ubiquitous components of most aquatic environments, and their burgeoning prevalence is endangering aquatic organisms. Recent studies have documented the entanglement of marine and freshwater biota by plastic litters, particularly ghost fishing gear, resulting in suffocation, drowning, or starving to death. Numerous reports have shown that aquatic organisms readily ingest and accumulate these emerging contaminants in their digestive systems. Given experimental evidence that contaminants-laden MNPs can persist in the gastrointestinal tract for considerable durations, investigations have documented a high probability of lethal and sublethal toxicological effects associated with direct and indirect MNPs ingestions. These include chronic protein modulation, DNA damage, embryotoxicity, gastrointestinal toxicity, genotoxicity, growth inhibition toxicity, histopathotoxicity, liver toxicity, neurotoxicity, oxidative stress, reproductive toxicity, and tissue damage. Today, reports have proven the transfer of MNPs across the aquatic food web to humans. However, the mechanisms of multiple contaminants-laden MNPs-induced toxicities, size-dependent toxicity, and the comprehensive mode-of-action and alterations of digestive, reproductive, and neurological systems’ functionality in marine organisms are still unclear. Thus, this review mainly addresses the prevalence, food web interactions, and toxicity assessment of micro(nano) plastics in marine and freshwater organisms. It summarizes documented studies based on the following broad objectives: (1) the occurrence and prevalence of micro(nano) plastic particles in marine and freshwater environments; (2) the ingestion of MNPs by aquatic biota and the food web exposure routes and bioaccumulation of contaminated MNPs by higher trophic entities; (3) the adsorption and desorption of persistent organic pollutants, metals and chemical additives on/from micro(nano)plastics; and (4) the probable ecotoxicological effects of micro(nano)plastics ingestion on aquatic biota.